Educational CornerBrachytherapy in paediatric malignancies – review of indications - Fijuth, Jacek (Journal of Contemporary Brachytherapy, 2010)
Paediatric malignancies are relatively rare, with an annual frequency of 13-14 in 100 000 children up to 15 years, and account for less than 1% of all cancer in developed countries. Paediatric tumours are generally managed with a multi-modality treatment programme that includes surgery, chemotherapy, and external beam radiation therapy (EBRT). Treatment strategies directed towards the reduction of late side effects have significantly increased interest in brachythe-rapy, in particular of soft tissue sarcoma and clear cell adenocarcinoma, as in these malignancies often only a limited target volume needs to be treated by a significant radiation dose. Current indications for brachytherapy in paediatric malignancies are presented briefly in this study.